Promoting positive beliefs toward research evidence: results from a utility-value intervention study with pre-service teachers - Maximilian Knogler; Ricardo Böheim; Annika Diery; Judith Harackiewicz; Tina Seidel (Frontiers in Psychology)
Pre-service teachers often question the relevance of educational evidence for professional practice. Yet, according to expectancy-value theory, the extent to which pre-service teachers consider educational evidence relevant for their teaching practice (i.e., utility-value) is a critical variable in promoting evidence-based practice in education. To further promote utility-value of research evidence among pre-service teachers, the present study investigated the added value of a brief and easy-to-implement intervention that stimulates students to reflect on the utility-value of research evidence. The sample consisted of 3rd semester pre-service teachers (N = 61) enrolled in a semester-long course on effective teaching who were randomly assigned to two conditions. In the first condition (default course design), teacher educators used two typically applied strategies for promoting utility-value, i.e., direct communication of utility-value and application tasks, in which students can discover utility-value. In the second condition (enhanced course design), students were additionally stimulated to reflect on the utility-value in two written assignments. Their value perceptions and related variables were measured at the beginning, during and at the end of the semester. Although a mixed model MANOVA did not yield a statistically significant group-by-time interaction effect, follow-up t-tests revealed a substantial and significant increase in students value perceptions in the enhanced course design, but not in the default course design. Overall, this study offers some limited support for the additional value of reflective writing assignments for fostering pre-service teachers' positive beliefs toward research evidence in education.